Perceptions on barriers and opportunities for integrating urban agri-green roofs: A European Mediterranean compact city case. (July 2021) - Zambrano-Prado, Perla; Pons-Gumí, David; Toboso-Chavero, Susana; Parada, Felipe; Josa, Alejandro; Gabarrell, Xavier; Rieradevall, Joan
Abstract: The main objective of this study is to analyze the perceived barriers and opportunities with regard to the implementation of urban agri-green roofs (UAGR) in cities. The case study was conducted in Barcelona, a Mediterranean compact city. The World Café method was used in this work. Five categories of barriers and opportunities were discussed (social, environmental, legal/administrative, technological/architectural, and economic) by interdisciplinary stakeholders. A total of 129 barriers and opportunities were identified. The main barriers identified were as follows: the lack of information and social cohesion regarding UAGR projects; the Mediterranean climate; the lack of specific regulations and protocols; the initial investment; and the pre-condition of the roof and its load bearing capacity. The main opportunities were social cohesion; improved life quality; new specific regulations; the profits derived from UAGR projects; and aesthetic improvement. The UAGR's scale of impact results showed a homogeneous distribution between "building" and "city", while the "global" scale remains residual. Regarding the stage of the UAGR life cycle at which barriers and opportunities emerge, the results highlight how most opportunities appear during the "use" stage of the roof, whereas barriers do so during the "project" stage. Highlights: Social cohesion is emphasized as an opportunity by all stakeholders. Barriers mainly appear during the project stage of urban agri-green roofs. Most opportunities are present in the use stage of urban agri-green roofs. Financial incentives should not be exclusively based on the stage of construction. Governmental support is key to improve education and awareness of UARG benefits.